A cadeia produtiva da borracha natural brasileira - Lima, Paulo Henrique Silveira (2016)
This thesis analyzes the productive chain of Brazilian natural rubber. As natural rubber have properties that no other product they have, such as resilience, anti-abrasiveness, isolation, impermeability to liquids and gases, is an irreplaceable and strategic product. Therefore, besides being used to manufacture more than forty thousand objects, it is essential to human mobility, since it is the main component in the manufacture of tires used in world transport, to bicycle until plane, besides the aerospace craft and the seals in aquatic transport.Since the current technical-scientific-information period information is based on communication and circulation, natural rubber is an indispensable product. Thus, this thesis investigates the reasons for Brazil, country of origin of the rubber tree, have lost their productivity and competitive, left hegemonic be and exporter, while Southeast Asian countries who illegally took the rubber tree seeds from Brazil took the hegemony of production of natural rubber consumed in the world market. The general objective wasto analyze the productive chain of the Brazilian natural rubber, demonstrating that the form of the use of science, technology and productive regions of the country, have been decisive in the results productivity and competitiveness of the entire production chain.The concept has been used to link the various stages and actors involved in the production, distribution, marketing, technical assistance, credit, etc. and the consumption of a particular commodity, to enable a systemic rather than piecemeal the various stages through which a product passes before reaching the consumer final.This concept was used in this thesis as systemic and prospective production tool to represent the natural rubber in Brazil, led by global hegemonic agents, represented by large pneumatic industrial networks, but with the growing stage of rubber being processed locally by family farms and factoryand/or systems agroindustry.The methodology used in this thesis was the collection of specific magazines, articles and scientific papers, official and private sites, and rubber plantations visits, participation in conferences and research and interviews. The results were tabulated in charts, tables, maps and photographic panels. One of the main conclusions was that while Asian countries who illegally took rubber tree seeds from Brazil produce about 93% of global natural rubber, Brazil that has produced 100% of that currently produces 1%; and entire northern region that has produced 100% natural rubber in the country currently produces about 3%. While only the state of São Paulo already produces 54% of this total, making it the leading producer in the country, followed by Bahia 17%. The explanation is that in the production chain of natural rubber in Asia and the productive regions of the chain in São Paulo and Bahia the state programs and business with contribution of science, technology and innovation were decisive to this good productivity and competitiveness. Because these technologies are not equally distributed in the various Brazilian productive regions, and not in all sectors of the chain, the country has had low productivity and competitiveness. Even the modern networks of pneumatic Brazil, the sector with the best productive capacity of the chain, are losing competitiveness for pneumatic Europe and Asia countries.